Application of biomimetic structural concept in bone tissue engineering scaffolds - WANG Yun; WANG Zuolin (Kouqiang hemian waike zazhi)
The influence of component composition, pore size, porosity, and mechanical properties of bone tissue engineering (BTE) scaffolds on bone regeneration has been extensively studied. However, there is currently a lack of research on the impact of multi-scale structural design on bone regeneration. With the advancement of biomimetic technology, mimicking the multi-scale structures of natural materials presents a promising strategy to enhance the mechanical performance and biological activity of BTE scaffolds and facilitate bone regeneration. As such, this review provides a summary of recent advances in biomimetic structural materials utilized in BTE scaffolds, discussing future development opportunities and challenges with the aim of inspiring the design of BTE scaffolds with superior properties.